The Modernization of Civil Law Institutions: Civil Liability, Property and Contract (2019)
Civil liability, the transfer of property rights, and contractual modernization have been difficult issues for legal treatment due to their permanent jurisprudential evolution and the variety of doctrinal studies that seek to establish their development and modern interpretation. The dynamics of civil liability requires a permanent adaptation to constant social changes, advances in science and technology, due to which this issue has an important impact inside and outside of private law. Based on the previous premises, this research book aims to present the most transcendent difficulties of the general theory of the law of damages, by studying risk at the jurisprudential level, the method to transfer property in the field of international trade, as well as the notion of civil liability in Europe and Latin America, which contributes to a broader view on the determination and prevention of damage. Undoubtedly, the result is a dogmatically enriching and useful text, both for students and law practitioners, who usually face problems that need to be analyzed in a modern way, in light of the fundamentals of civil liability. (Taken from source).